Peran Public Relations Dalam Menumbuhkan Citra Perusahaan Yang Positif - Miko Ibnu Ibrahim (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In the current era of digital communication and information, public relations (PR) is very important to build a positive company image. PR manages relationships between businesses and various stakeholders, such as the media, investors, consumers and the wider public. PR can build a positive image of a company through various activities, such as product launches, social activities, and responding to controversial issues. Through mass media, digital platforms and special events, PR can increase trust, increase brand awareness and manage crises. In the competitive world of business, the positive image built by PR can be a valuable asset that differentiates a company from its competitors, increases customer loyalty, and drives growth. Therefore, for companies that want to improve their reputation and business sustainability, the PR function is a strategic step that must be taken.